2005
DOI: 10.1038/nature04349
|View full text |Cite
|
Sign up to set email alerts
|

Complex organic matter in Titan's atmospheric aerosols from in situ pyrolysis and analysis

Abstract: Aerosols in Titan's atmosphere play an important role in determining its thermal structure. They also serve as sinks for organic vapours and can act as condensation nuclei for the formation of clouds, where the condensation efficiency will depend on the chemical composition of the aerosols. So far, however, no direct information has been available on the chemical composition of these particles. Here we report an in situ chemical analysis of Titan's aerosols by pyrolysis at 600 degrees C. Ammonia (NH3) and hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(132 citation statements)
references
References 27 publications
8
124
0
Order By: Relevance
“…The ability for ammonia oxidation is not necessarily an advantage for the survival on the Red Planet, but could be beneficial when introduced in the environments of the Saturn's moons Titan or Enceladus. Although the temperature on both moons is quite low, the presence of ammonia, H 2 O and other prerequisites for a possible growth of specialized microbes has been discussed (Israel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The ability for ammonia oxidation is not necessarily an advantage for the survival on the Red Planet, but could be beneficial when introduced in the environments of the Saturn's moons Titan or Enceladus. Although the temperature on both moons is quite low, the presence of ammonia, H 2 O and other prerequisites for a possible growth of specialized microbes has been discussed (Israel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We then compare our results with a) the spectral characteristics of laboratory-made tholins reported in the literature (e.g., Khare et al 1984;Quirico et al 2008;Gautier et al 2012); b) those derived from highaltitude (600−1250 km) emission observed by Cassini/VIMS López-Puertas et al 2013); and c) the low-altitude (20−130 km) results from the Huygens/Aerosol Collector and Pyrolyser (ACP; Israël et al 2005). …”
Section: Introductionmentioning
confidence: 89%
“…This supports the tholin hypothesis. From these new in situ measurements it seems very likely that the aerosol particles are made of a refractory organic nucleus, covered with condensed volatile compounds [18].…”
Section: A Complex Prebiotic-like Chemistrymentioning
confidence: 96%